Mayonnaise Enriched with Flaxseed Oil: Omega-3 Fatty Acids Content, Sensory Quality and Stability during the Storage - Mohammed El-Waseif; Badr Saed; Hany Fahmy; Ahmed Sabry; Hamdy Shaaban; Mohamed Abdelgawad; Ali Amin; Amr Farouk (Foods, 2022)
This study aimed to produce healthy mayonnaise with a protective effect against cardiovascular diseases, containing omega-3 fatty acids (FA), using flaxseed oil (FXO), which includes a high percentage of alpha-linolenic acid (ALA, C18:3n-3). The mayonnaise was prepared by replacing soybean oil with FXO at 20, 30, and 40% levels. The effect on the organoleptic, physical, and chemical quality was studied compared to a control, prepared only with soybean oil (70%). The oxidative and microbial stability during 12 weeks of storage at 25 and 7 °C was also evaluated. The results showed that the use of FXO in mayonnaise (20, 30, and 40%) led to an increase in TUFA (from 79.37 (control) to 82.48, 85.49, and 87.66%, respectively), particularly in PUFAn-3, due to the rise of ALA (from 6.5 to 18.38, 24.02 and 37.87%, respectively) and a decrease in TSFA (from 20.63 to 17.52, 14.51 and 12.34%, respectively). The panelists did not perceive significant differences in the sensory characteristics of the “new” mayonnaise. A decrease in the oxidation rates of the “new” mayonnaise during the storage period was observed. A significant effect on microbial growth was not reported, although the permissible limits were not exceeded after 12 weeks of storage, even at 25 °C.